2021
DOI: 10.1109/jstars.2020.3041162
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Smartphones Into Small Unmanned Aircraft Systems to Sense Water in Soil by Using Reflected GPS Signals

Abstract: We investigate the feasibility of using built-in GNSS sensors within ubiquitous smartphone devices from a small UAS for the purpose of land remote sensing. We summarize the experimental findings and challenges that need to be resolved in order to perform the GNSS Reflectometry (GNSS-R) technique via smartphones. In late 2018, a series of experiments was conducted and designed by integrating two smartphones into a multi-copter UAS by attaching them to ground plates to isolate and record both direct and reflecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Comparisons between the proposed antenna and other reference antenna designs for UAV applications are given in Table 1 , where λg is the guided wavelength of the antenna medium. As the navigation satellite signal is of CP senses, the ones reported in References 5, 6, 8 will exhibit a polarization loss factor equal to 0.5 because they are LP antennas. This causes the LP antenna built on the UAV to receive only half of the power transmitted by the satellite's CP antenna.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparisons between the proposed antenna and other reference antenna designs for UAV applications are given in Table 1 , where λg is the guided wavelength of the antenna medium. As the navigation satellite signal is of CP senses, the ones reported in References 5, 6, 8 will exhibit a polarization loss factor equal to 0.5 because they are LP antennas. This causes the LP antenna built on the UAV to receive only half of the power transmitted by the satellite's CP antenna.…”
Section: Resultsmentioning
confidence: 99%
“…The applications of unmanned aerial vehicles (UAV) are becoming very popular in recent years as they can be used for military and civilian purposes. In military applications, UAVs can be used for training, reconnaissance, logistics, and combat 1 ; for civilian purposes, the typical applications include traffic monitoring, 2 precision agriculture, 3 infrastructure measurement, 4 tracking and surveillance, 5 scientific research, 6 search and rescue, 7 and so on. Depending on the purpose of the UAV, different equipment or sensors may be installed, or different communication frequency bands may be used.…”
Section: Introductionmentioning
confidence: 99%
“…Several works have proven the efficiency of GPUs in GNSS-R receivers. It should be noted that mobile phones can also be receivers to sense water and soil via GNSS-IR [41,105,106].…”
Section: Cgnss-r Altimetrymentioning
confidence: 99%
“…Two smartphones were connected to the upper and lower sides of the plane, allowing for the isolation and recording of the direct and reflected GNSS carrier noise density ratios as well as the remote sensing of land surface data. The results revealed that the reflected signals exhibited geographical correlations in line with surface properties, including the pond’s high reflectivity, susceptibility to different types of land crops, and soil wetness [ 20 ]. When an electromagnetic wave shines on a dielectric material—that is, when it passes through the upper dielectric and is reflected by the lower dielectric—it exhibits the phenomena of the complete transmission.…”
Section: Introductionmentioning
confidence: 99%